Rare Case Of Neurofibroma Of Eye Lid - Raval, Nidhish; Jadhav, Renuka; Pande, Vineeta; Mane, Shailaja; Karthik D, Karthik D (Journal of Neonatal Surgery, 2025)
Neurofibromatosis type 1 (NF1) is a genetic neurocutaneous disorder with autosomal dominant inheritance, primarily affecting the skin, nervous system, and eyes. Ocular manifestations include optic pathway gliomas, Lisch nodules, and plexiform neurofibromas etc., In the present case, a solitary neurofibroma was seen on the upper eyelid of a 10-year-old male which impacted his vision. Surgical excision and histopathological analysis confirmed a plexiform neurofibroma. Early recognition of NF1-associated eyelid tumors is crucial for preventing vision impairment, and recent imaging advances support improved diagnostic accuracy for NF1’s ocular features